Analysis of warm and cool events in the Gulf of Papagayo through diving data: A Citizen Science approach - Escoto-Murillo, Andrés; Alfaro, Eric-J. (Revista de Biología Tropical, 2021)
Introduction: In January 2011 and as a Citizen Science initiative, the owners of the Deep Blue Diving Shop in Playa del Coco, Guanacaste, Costa Rica, began to collect daily temperature data in the seawater column during their diving activities, to inform tourists before traveling to Costa Rica and help them properly select their diving equipment and thus maximize the enjoyment of the experience in the Gulf of Papagayo. This data collection remained constant until January 2020 due to the COVID-19 pandemic. Objective: Identify cold and warm events of the sub-surface temperature of the sea in the Gulf of Papagayo, Guanacaste, Costa Rica and their relationship with known sources of climate variability as El Niño-Southern Oscillation (ENSO) and synoptic systems such as incursions of cold fronts in the Caribbean Sea. Methods: Sea Subsurface Temperature data corresponding to the lowest temperature of the seawater column were used, at an approximate depth of 25-35m. Observations were made daily, from 01/01/2011 to 01/31/2020. Results: The mean temperature was 25.7 °C. Cooler temperatures were observed in February-March, below 22.5 °C with a secondary minimum in July. There were two peaks in May and August with temperatures above 27.4 °C. The drops during cold events reached 16-17 °C. All cold events were associated with the passage of cold fronts through the Caribbean Sea, due to reinforcement in the intensity of the trade winds, with a zonal component from the East, which causes seasonal upwelling. The warm events presented temperatures at their maximum of 30-31 °C. The latter events were associated with the development and maturity of warm El Niño-type ENSO events. ENSO is an important modulator of sea temperature variability in the Gulf of Papagayo, since El Niño events are related to positive anomalies in sea temperature in the Eastern Tropical Pacific. Conclusions: The Citizen Science initiative presented in this study proved to be very useful for monitoring sea temperature in the Gulf of Papagayo. The results of this study indicate that Dive Masters can provide data on sea temperature of sufficient quality and with high temporal resolution. Divers can profitably support monitoring and Citizen Science can contribute positively to social well-being by influencing the questions that are being addressed and by giving people a voice in local environmental decision-making. The information generated in this study returns to the tour operators and enhance the understanding of the variability observed in the data collected by them, a knowledge that is later transmitted to their clients to improve their experience.